Kinematics of sprinting in different assisted conditions compared to normal free sprinting in trained athletes - Birklbauer, J.; Kratky, S.; Kreuzhuber, D.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to examine the kinematics of sprinting under different assisted conditions as compared to free sprinting in the top-speed phases. 13 trained athletes performed one trial of each of 4 conditions: with a rope-and-pulley towing device (TD); with a special sprint parachute causing a lift effect (SC); with both training devices combined (TD+SC) and in a normal free sprinting condition (FS). Average and maximum speed were measured with light barriers and a laser system. Stride length, stride frequency, contact time and flight time were collected with an optical acquisition system for eight strides. Statistical analysis found significant differences in TD, SC and TD+SC compared to FS for running speed (except TD+SC) and stride length, whereas stride frequency was significantly altered only in SC condition. Contact time significantly changed exclusively in TD+SC, shortened by 5 ms (4.5%). Further research is needed to clarify neuromuscular adaptations and controlled training studies have to be done to prove the usefulness of these training devices.